ACEP Emergency Department COVID-19 Management Tool: A Review of the Updated Guidelines. (October 2021) - Hill, April Turner
Abstract : This review examines the American College of Emergency Physicians' (ACEP) Emergency Department COVID-19 Management Tool (2021). The authors and contributors developed a tool to provide a framework to assist with severity classification, risk assessment, diagnostic workup, disposition, and treatment of patients with suspected or confirmed COVID-19 in the emergency department. By utilizing the tool from this study, the emergency nurse practitioner can confidently treat COVID-19 and reduce patient risks from unnecessary treatments or unneeded admissions.